Gamificación como estrategia didáctica para motivar el aprendizaje en los estudiantes de Básica Superior - Chavez Angulo, Carola Concepcion; Jara Pacheco, Lia Del Rocio; Santamaria-López, Teresa; Pérez Barrera , Hendy Maier (Revista Minerva, 2025)
This research focuses on evaluating whether gamification in classes increases students’ motivation and participation, thus improving their academic performance. The effects of gamification on intrinsic and extrinsic motivation are analyzed, seeking to align the educational process with current student expectations. The general objective of this study is to determine how gamification can motivate the learning of Upper Basic students. Specific objectives include theoretically justifying the use of gamification, diagnosing the current level of student motivation, designing a didactic proposal based on this strategy, and evaluating its effectiveness. The research used an experimental design with 94 students from the Montalvo Educational Unit, divided into two groups: one experimental (with gamification) and one control (traditional teaching). Exploratory, bibliographical, and field methods were applied, using surveys to collect data. The analysis was mixed, focusing on variables such as motivation and participation. The results showed that 47.31% of the experimental group reported high motivation with tools like Socrative, compared to 26.69% of the control group. Furthermore, 53.07% of the experimental group felt that these strategies improved their understanding in the social studies subject, compared to 29.90% of the control group. Participation was also significantly higher in the experimental group (73.4% vs. 13.2%). Finally, 87.2% of the experimental group noticed improvements in their academic performance after the intervention. It is recommended to regularly incorporate gamification in education to meet the current needs of students.